CDK6 is essential for mesenchymal stem cell proliferation and adipocyte differentiation - Hu, Alexander J.; Li, Wei; Pathak, Apana; Hu, Guo-Fu; Hou, Xiaoli; Farmer, Stephen R.; Hu, Miaofen G. (Frontiers in Molecular Biosciences, 2023)
Overweight or obesity is a risk of many obesity-related metabolic diseases. Among all the potential new therapies, stem cell-based treatments hold great promise for treating many obesity-related metabolic diseases. However, the mechanisms regulating adipocyte stem cells / progenitors (precursors) are unknown. In the current study, we found that mice with a kinase-inactive cyclin-dependent kinase 6 (CDK6) mutants (K43M) had fewer precursor residents in the stromal-vascular fraction (SVF) of adult white adipose tissue (WAT). Adipocyte-derived stem cells (ADSCs) from the SVF or mouse embryonic fibroblasts (MEFs) from K43M mice had defects in proliferation and differentiation into the functional fat cells. In contrast, mice with a constitutively active kinase CDK6 mutant (R31C) had the opposite traits. Ablation of RUNX1 in both mature and precursor K43M cells, reversed the phenotypes. These results represent a novel role of CDK6 in regulating precursor numbers, proliferation, and differentiation, suggesting a potential pharmacological intervention for using CDK6 inhibitors in the treatment of obesity-related metabolic diseases.